Peer Mentorship in Nursing Education: A Scoping Review on the Impact on Mentors - Dauk, Sarah; Bergen, Tania; Juckes, Karen; Rodger, Kathleen (Quality Advancement in Nursing Education / Avancées en formation infirmière, 2026)
A scoping review was undertaken to explore the literature on the role of the peer mentor during undergraduate nursing education in order to determine the personal and professional impacts of participating in this role. Much is known about the benefits of being mentored as a nursing student (Botma et al., 2013; Jacobs, 2017). However, less is written about how peer mentorship affects those who provide mentoring, particularly when the mentors are students themselves. We performed a search and analysis of literature in the method outlined originally by Arksey and O’Malley (2005) and updated by Peters et al. (2024) for the Joanna Briggs Institute for Evidence Synthesis. Key findings from this review indicate that nursing students who participate as mentors gain communication and leadership skills, increase their understanding and ability to perform various nursing roles, improve their self-confidence and self-esteem, and feel a greater sense of belonging in their academic program and in the nursing profession. Challenges of peer mentoring included feelings of insecurity, navigating difficult mentee behaviours, and managing the time requirement amid a busy academic load. Recommendations identified from the literature include providing education and faculty support for mentors, embedding mentorship into undergraduate nursing curriculum, and embarking on longitudinal research to follow mentors into practice and identify long-term impacts of peer mentorship. The benefits of being a peer mentor align well with curriculum outcomes of undergraduate nursing programs and entry-level competencies for registered nurses in Canada, making peer mentorship a relevant and efficacious strategy for nursing programs to meet the educational demands of preparing nursing graduates who are ready for practice.